Cultivating Resilience: A Key to Managing Academic Stress among Health Students in Online Learning - Abdillah, Hafizh Zain; Marleni (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Academic stress refers to the pressure a person faces when dealing with academic demands. It is characterized by a variety of reactions, including physical, emotional, cognitive, and behavioral responses. The aim of this research is to empirically test the extent to which resilience contributes to academic stress among health students taking online learning at